ORDINARY CHANGES IN SCHOOL ADMINISTRATION: THE IMPLEMENTATION OF DEMOCRATIC MANAGEMENT IN MUNICIPAL ELEMENTARY SCHOOLS IN THE CITY OF ASTORGA-PR (2004 - 2015) - Silva, Adriana Stoppock; Rossi, Edneia Regina [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2022)
This article analyzes how the goal of democratic management, established as a law by the Municipal Education Plan of Astorga (PME-Ast, in Portuguese), was appropriated and implemented by school principals in the municipality of Astorga, Parana, Brazil. The research is of qualitative and descriptive nature. The methodology used was content analysis, as proposed by Laurence Bardin (1977), comprising pre-analysis, material exploration, treatment of results, inference, and interpretation. The sources used were Law number 9.394/96, or the Law of Directives and Bases of National Education (LDBEN, in Portuguese), the National Education Plan (PNE, in Portuguese), the Municipal Education Plan of AstorgaPR (PME-Astorga, in Portuguese), the regulations of municipal schools of Elementary Education and the records from the Municipal Council of Education from 2004 to 2015, in addition to semi-structured interviews with the school principals of municipal schools and the then director of the Municipal Department of Education. In the interpretation stage, the concept of appropriation of Chartier (1990) allowed for analyzing the discontinuity between the ideals and the uses made of the PME-Astorga by the school principals. As a result, it was identified that, although the school principals had the knowledge and access to the mentioned plan, not all of them understood in the same way regarding the use of its definitions in everyday school situations. Difficulties and insecurities for its implementation were mentioned, although changes in power relationships in the school are explained, from more authoritarian postures to decisions of more collective nature. Elections for school principals would have reduced the interference of local power structure within the schools. The collegiate instances of discussions and the involvement of different individuals were the elements of change most remembered by the managers. However, although they recognize the openness to participation, they reveal that the engagement of the individuals would be scarce, which requires the constant mobilization of strategies so that some involvement takes place.
Keywords: Municipal Education Plan; Implementation of Democratic Management; History of the present time; Municipality of Astorga-Parana